Developing O Diadaq O Dibiasa Text Reading Comprehension Activities To Students of Madrasah Aliyah and Boarding School - Ahmad Muaffaq; Rabiatul Adawiah; Syamsinar Syamsinar; Muhammad Nur Murdan (MATAPPA: Jurnal Pengabdian Kepada Masyarakat, 2021)
The objective of this social engagement project is to design the developing of O Diadaq O Dibiasa text as material in reading comprehension activities to students of Madrasah Aliyah and Islamic Boarding School in West Sulawesi. Beside that mayor objectives, there are also some specific objectives such as to outline the integration of Islamic and local values in O Diadaq O Dibiasa text; and to see the improvement of students’ knowledge related to the integration of Islamic and local values after reading O Diadaq O Dibiasa text.This project was conducted through Whatsapp, Zoom and Google Meet application remembering the situation of Covid-19 pandemic. It was held on February-September including preparation until evaluation. There were five steps in conducting this social engagement. They are visiting libraries, training of trainers, writing module, conduction reading activities (5 meetings), and monitoring & evaluation. The participants were 20 students from Madrasah Aliyah Pergis Campalagian Boarding School of DDI Baruga Majene, Madrasah Aliyah 1 Polewali Mandar and Boarding School of Syekh Hasan Yamani Campalagian Polewali Mandar which are represented by five students.